2023
DOI: 10.1002/ijc.34442
|View full text |Cite
|
Sign up to set email alerts
|

Molnupiravir is effective in patients with haematological malignancies

Abstract: Patients with hematologic malignancies are particularly vulnerable to severe infectious complications. SARS‐CoV‐2 infection is associated with a high risk of severe course and death in this patient population. In addition, immune deficits associated with both the blood cancer and the treatment used make vaccination against SARS‐CoV‐2 less effective than in immunocompetent individuals. Molnupiravir is one of the first oral antiviral drugs to demonstrate a significant benefit in reducing hospitalisation and deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a cohort of 175 hematological patients treated with Molnupiravir, of whom 77% were vaccinated, the rates of hospitalization and death at 28 days were 20% and 4% respectively. These outcomes were better than those previously reported in vaccinated hematological patients [120]. A matched-paired analysis from the EPICOVIDEHA registry, comparing the use of Molnupiravir versus Nirmatrelvir/ritonavir in 232 patients with HM (including only 9 with CLL), reported similar rates of SARS-CoV-2 severity, hospitalization or mortality between the two drugs [121].…”
Section: Other Strategies To Mitigate Risk Of Severe Infectionmentioning
confidence: 78%
“…In a cohort of 175 hematological patients treated with Molnupiravir, of whom 77% were vaccinated, the rates of hospitalization and death at 28 days were 20% and 4% respectively. These outcomes were better than those previously reported in vaccinated hematological patients [120]. A matched-paired analysis from the EPICOVIDEHA registry, comparing the use of Molnupiravir versus Nirmatrelvir/ritonavir in 232 patients with HM (including only 9 with CLL), reported similar rates of SARS-CoV-2 severity, hospitalization or mortality between the two drugs [121].…”
Section: Other Strategies To Mitigate Risk Of Severe Infectionmentioning
confidence: 78%
“…Additionally, early therapeutic strategies, particularly the use of targeted antivirals and monoclonal antibodies, were crucial in enhancing patient outcomes. 35 , 36 , 37 These early treatments not only reduced the severity of the illness but also led to decreased mortality rates. 10 , 11 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…There was no increase in the incidence of adverse events in the molnupiravir 800 mg/day group compared to 200 mg/day and 600 mg/day groups [ 90 ]. The efficacy of molnupiravir and its favorable safety profile were also confirmed in patients with HM [ 58 ]. Other publications indicated that the use of molnupiravir in patients with severe or moderate COVID-19 did not bring clinical effects [ 91 ].…”
Section: Molnupiravir (Lagevrio)mentioning
confidence: 99%